Challenges and opportunities for tobacco control in Australia: a qualitative study - Michelle I. Jongenelis (Elsevier, 2022)
Abstract Objective: A greater understanding of the challenges and opportunities for tobacco control in Australia can assist with accelerating efforts in this space. This study sought to explore these challenges and identify priorities for policy and practice. Methods: Interviews were conducted with 31 individuals working in tobacco‐ and/or nicotine‐related research, policy and practice in Australia. Interviewees were tobacco control and cessation advocates, researchers, public servants and health practitioners representing a range of government and non‐government organisations. Results: Commonly reported challenges included e‐cigarettes distracting from evidence‐based reform, lack of government investment, a misperception that tobacco control is 'done' and tobacco industry interference. Advocating for tobacco control to be high on political agendas, sustained investment in evidence‐based measures, improved support for cessation and addressing industry interference were considered important means of addressing these challenges. Conclusions: Several challenges are perceived to be hampering Australia's tobacco control efforts. The attention being devoted to e‐cigarettes at the expense of effective control measures warrants immediate addressing. Implications for public health: Increasing awareness that smoking continues to be the leading cause of preventable death, developing an evidence‐based national cessation strategy and implementing measures that protect tobacco control efforts from vested interests are critical to reducing smoking prevalence rates.